A companion to early modern Spanish imperial political and social thought - Tellkamp, Jörg Alejandro (Brill, 2020)
"This Companion aims to give an up-to-date overview of the historical context and the conceptual framework of Spanish imperial expansion during the early modern period, mostly during the 16th century. It intends to offer a nuanced and balanced account of the complexities of this historically controversial period analyzing first its historical underpinnings, then shedding light on the normative language behind imperial theorizing and finally discussing issues that arose with the experience of the conquest of American polities, such as colonialism, slavery or utopia. The aim of this volume is to uncover the structural and normative elements of the theological, legal and philosophical arguments about Spanish imperial ambitions in the early modern period."
Keywords: Geschichte 1500-1700; Kolonialismus; Imperialismus; Politische Theorie; Ethik; Rechtfertigung; Spanien; Spain / History / House of Austria, 1516-1700; Spain / Politics and government / 1516-1700; Spain / Intellectual life / History / 16th century; Intellectual life; Politics and government; Spain; 1500-1700; History; Aufsatzsammlung